Review: F-actin remodelling during plant signal transduction via biomolecular assembly - Ma, Zhiming (2022)
During signal transduction, multivalent interactions establish dynamic molecular connectivities that propagate molecular cascades throughout the entire signaling pathway. Such multivalent interactions include the initial activation, cascade signal transduction, and the amplification and assembly of structural machinery. For example, plants rapidly remodel the actin cytoskeleton during signal transduction by perceiving a wide range of mechanical and chemical cues from developmental and defense pathways. Actin treadmilling is stepwise-regulated by interactions between actin and actin-binding proteins (ABPs). Emerging evidence shows that intrinsically disordered regions (IDRs) enable flexible and promiscuous interactions that serve as the functional hub for generating cellular interactomes underlying various signaling events. Though IDRs are present in a majority of ABPs, few of the functional roles of IDR in the interaction and functions of ABPs have been defined. The distinct features of IDRs create diverse and dynamic molecular interactions that introduce a new paradigm to our understanding of the structure-function relationships for actin assembly. In this review, we will create a snapshot of recent advances in IDR-mediated plant actin remodeling and discuss future research directions in studying the complexity of actin assembly via multifaceted biomolecular assembly during signal transduction.